Pemberdayaan Kader Kesehatan melalui Optimalisasi Pengawasan Konvensional dan Pendampingan Buku KIA dalam Asuhan Ibu Nifas Risiko Tinggi di Wilayah Dinas Kesehatan Kota Salatiga - Diah Winatasari; Citra Elly Agustina; Retnaning Muji Lestari (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The postpartum period is a critical time associated with various health risks, particularly for high-risk mothers. Limited healthcare personnel available for monitoring necessitates the empowerment of community health volunteers (*kader*) to assist with early detection and support for postpartum mothers. This initiative aimed to enhance the capacity of these volunteers by optimizing conventional monitoring methods and guiding the use of the Maternal and Child Health (MCH) Handbook (*Buku KIA*) in the care of high-risk postpartum mothers in Salatiga. An active participatory partnership approach was employed from August to November 2025, comprising three stages: preparation and coordination, volunteer training, and guidance and supervision of home visits. The program involved volunteers, high-risk postpartum mothers, university students, and faculty members. Results demonstrated improved volunteer knowledge and skills regarding the detection of postpartum danger signs and the use of the MCH Handbook as a monitoring tool. All volunteers accurately completed monitoring forms and provided support in accordance with postpartum care standards. This support contributed to adherence to postpartum visit schedules, successful physical recovery, smooth lactation, and the absence of maternal complications or psychological issues.